EFFECTS OF CROSS-LINGUISTIC INFLUENCES ON SECOND LANGUAGE ACQUISITION: A CORPUS-BASED STUDY OF SEMANTIC TRANSFER IN WRITTEN PRODUCTION - María del Mar Ramón Torrijos (Revista de Lingüística y Lenguas Aplicadas, 2009)
This article concentrates on the impact that cross-linguistic influences have on second language acquisition. It investigates the importance of the learner's native language (L1) in written production of a second language (L2), particularly the use of L1 linguistic rules by Spanish speakers when they are writing in the target language (L2). This exploratory research focuses on the production errors made by students relative to specific subsystems such as semantic and syntactic areas. Errors are studied with respect to the differences between Spanish and English through a contrastive analysis between both languages in problematic linguistic areas. In this article only semantic errors will be considered as a first approximation to the study of transfer in written production. The results indicate that transfer is a reality and an important determinant in the process of second language acquisition. Teachers in an EFL context should be able to identify this phenomenon in order to prevent the errors which may arise from it.